The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24065187
|View full text |Cite
|
Sign up to set email alerts
|

Young Astrocytic Mitochondria Attenuate the Elevated Level of CCL11 in the Aged Mice, Contributing to Cognitive Function Improvement

Abstract: Aging drives cognitive decline, and mitochondrial dysfunction is a hallmark of age-induced neurodegeneration. Recently, we demonstrated that astrocytes secrete functional mitochondria (Mt), which help adjacent cells to resist damage and promote repair after neurological injuries. However, the relationship between age-dependent changes in astrocytic Mt function and cognitive decline remains poorly understood. Here, we established that aged astrocytes secret less functional Mt compared to young astrocytes. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
(177 reference statements)
0
1
0
Order By: Relevance
“…More recently, others have observed that, alongside functional mitochondria, astrocytes also secrete the mitochondrial-genome-encoded small bioactive peptide humanin that is transported to microglia, reducing proinflammatory outcomes [ 312 ]. Notably, the efficacy of mitochondria transfer is intrinsically related to the age of the donor tissue/cell, as young mitochondria show better performance than older ones [ 313 ]. Corroborating these findings, mitotherapy with healthy young mitochondria obtained from the livers of young mice showed positive results in restoring the hippocampal mitochondrial bioenergetics of aged mice [ 314 ].…”
Section: Mitochondrial Transplantation: Could the Transfer Of Healthy...mentioning
confidence: 99%
“…More recently, others have observed that, alongside functional mitochondria, astrocytes also secrete the mitochondrial-genome-encoded small bioactive peptide humanin that is transported to microglia, reducing proinflammatory outcomes [ 312 ]. Notably, the efficacy of mitochondria transfer is intrinsically related to the age of the donor tissue/cell, as young mitochondria show better performance than older ones [ 313 ]. Corroborating these findings, mitotherapy with healthy young mitochondria obtained from the livers of young mice showed positive results in restoring the hippocampal mitochondrial bioenergetics of aged mice [ 314 ].…”
Section: Mitochondrial Transplantation: Could the Transfer Of Healthy...mentioning
confidence: 99%